2013
DOI: 10.1002/gbc.20061
|View full text |Cite
|
Sign up to set email alerts
|

Regional variation in the particulate organic carbon to nitrogen ratio in the surface ocean

Abstract: [1] The concept of constant elemental ratios in plankton communities-the Redfield ratio -is of central importance to ocean biogeochemistry. Recently, several studies have demonstrated regional differences in the plankton C:P and N:P ratio. However, less is known about potential systematic variations in the C:N ratio. Here we present an analysis of the particulate organic carbon to nitrogen ratio of 40,482 globally distributed samples from the upper 200 m of the ocean water column. Particulate organic carbon an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

11
171
1

Year Published

2014
2014
2018
2018

Publication Types

Select...
8
2

Relationship

1
9

Authors

Journals

citations
Cited by 145 publications
(183 citation statements)
references
References 48 publications
11
171
1
Order By: Relevance
“…If we assume that the low C:N ratio observed in high-latitude suspended particles 17 is also present in exported organic matter, the low (C:P) exp in high-latitude regions is consistent with the high-latitude dominance of diatoms, which have been shown to contribute export with low N:P ratios 18 . We also find extensive regional variation in (C:P) exp between the subtropical gyres.…”
mentioning
confidence: 69%
“…If we assume that the low C:N ratio observed in high-latitude suspended particles 17 is also present in exported organic matter, the low (C:P) exp in high-latitude regions is consistent with the high-latitude dominance of diatoms, which have been shown to contribute export with low N:P ratios 18 . We also find extensive regional variation in (C:P) exp between the subtropical gyres.…”
mentioning
confidence: 69%
“…This leads to a C/N ratio that is higher and much more variable in inland waters than in offshore oceans; there is also a sharp contrast in nutrient levels and water residence times between the two (Hall et al, 2007, Sterner et al, 2008Watanabe and Kuwae, 2015). Several studies suggest that the currently observed C/N ratio, and variations in it, are difficult to reconcile with the value estimated by Redfield (6.63-7.7), which was based on data 55 taken from ocean-surface plankton and deep, dissolved nutrients from 1898 to 1933 (Kokrtzinger et al, 2001;Schneider et al, 2004;Koeve, 2006;Sterner et al, 2008;Martiny et al, 2013a;2013b;DeVries and Deutsch, 2014;Watanabe and Kuwae, 2015). The factors influencing variations in C/N are complex; nitrogen and light limitation and phytoplankton can only explain approximately 20% of the variation in C/N on a global scale (Martiny et al, 2013b).…”
Section: Introduction 30mentioning
confidence: 95%
“…In carbon units, using the revised Redfield ratio of Anderson and Sarmiento (1994) of 106 : 16, new production estimated in this study was 4.3 ± 0.9 mol C m −2 yr −1 in 2003-2006 and 6.96 ± 1.3 mol C m −2 yr −1 in 1985-1988. Because of global and regional variations in the C : N ratio Martiny et al, 2013;Ono et al, 2001), there are additional uncertainties when converting nitrate fluxes to carbon fluxes. Additionally, as noted above, these rates represent new production derived from the physical vertical supply of nitrate over the northern half of the subtropical gyre.…”
Section: Comparison To Other Rates Of Biological Productivity At Batsmentioning
confidence: 99%